The Effect of Incorporating Ginger Extract (Zingiber officinale) to Cow Milk Kefir: An Analysis of Antioxidant and Microbiological and Physicochemical Characteristics - Putri Dian Wulansari; Novia Rahayu; Nurul Frasiska (ANIMAL PRODUCTION, 2020)
This study aimed to analyze the antioxidant activities and microbiological and physicochemical characteristics of cow milk kefir fortified with ginger extract (Zingiber officinale). The ginger extract was incorporated together with grain before the fermentation. The levels of ginger extract concentrate were 0, 0.5, 1.0, 1.5, and 2.0 % (w/w). The ginger used in this study is a thick ginger extract that is added before the kefir fermentation process. The result showed that a higher level of ginger extract added to the fermentation could improve the antioxidant activities of the cow milk kefir. The kefir sample fortified with 2.0% ginger extract produced the highest antioxidant activities, particularly DPPH IC50 (0.32%) and a total polyphenol of 0.72%. This study found that the higher the ginger extract level, the lower the total count, total LAB, and total yeast. The average value of physicochemical characteristics for free fatty acid, lactic acids, alcohol, and pH in the present study was 0.5503 mg/KOH, 1.0005%, 1.628 g/dL, and 4.42, respectively. In conclusion, the ginger extract was effective for producing kefir with high antioxidant activities (DPPH IC50) and total polyphenol.